Green Supply Chain Transformation and Its Impact on Environmental Performance in Semarang’s Culinary and Fashion SMEs - Saptianing; Andi Setiawan; Suwardi; Nanang Adie Setyawan (Cita konsultindo, 2025)
Environmental concerns have become increasingly prominent, as numerous phenomena underscore the critical relationship between human sustainability and environmental preservation. This awareness has extended into the business sector, where consumers now expect companies to implement environmentally responsible strategies, especially amid growing health and ecological concerns. This study investigates the impact of transforming Green Supply Chain Management (GSCM) practices on the environmental performance of culinary and fashion MSMEs in Semarang City. Using purposive sampling, data were collected from 100 respondents representing local MSMEs. The research employed two analytical approaches within the Structural Equation Modeling (SEM) framework: Confirmatory Factor Analysis and Regression Weight Analysis. The findings reveal that the implementation of GSCM positively influences environmental performance and contributes to the long-term sustainability of MSME operations. This study offers practical implications for local MSMEs to integrate green practices into their supply chains while enhancing business continuity. Furthermore, the results provide valuable insights for local government authorities to develop supportive policies and programs that encourage sustainable business practices. Overall, this research highlights the strategic importance of GSCM as a tool for improving environmental performance and maintaining competitiveness in a globalized economy.